Vedolizumab for acute gastrointestinal graft-versus-host disease: A systematic review and meta-analysis - Allen Cheng-Wei Li; Allen Cheng-Wei Li; Chen Dong; Soon-Tzeh Tay; Ashwin Ananthakrishnan; Kevin Sheng-Kai Ma; Kevin Sheng-Kai Ma; Kevin Sheng-Kai Ma (Frontiers in Immunology, 2022)
ObjectiveTo determine the safety and efficacy of vedolizumab for the prophylaxis and treatment of gastrointestinal involvement of acute graft-versus-host disease (GVHD) (GI-aGVHD).MethodsLiterature search within PubMed, EMBASE, Web of Science, and Cochrane Library for observational studies and clinical trials that evaluated the effect of vedolizumab on GI-aGVHD was done through 17 May 2022. A bivariate and random-effect meta-analysis derived the pooled observational percentages and pooled risk ratios (RRs) from baseline of primary endpoints including overall response, complete response, mortality, and adverse events.ResultsThere was a total of 122 participants in eight eligible studies, including one study on the prophylactic use of vedolizumab and seven studies on vedolizumab for the treatment of GI-aGVHD. Of seven studies that reported details on baseline grades of GI-aGVHD, a total of 47 patients (47.95%) were of stage 4, 31 patients (31.63%) were of stage 3, 10 patients (10.2%) were of stage 2, and 10 patients (10.2%) were of stage 1. The use of vedolizumab for the treatment of GI-aGVHD yielded a significantly improved objective response rate (ORR) at 14 days (pooled ORR = 60.53%, pooled RR = 14.14, 95% CI: 2.95–67.71), 28 days (pooled ORR = 50%, RR = 7.36, 95% CI = 2.14–25.37), and 12 months (pooled ORR = 76.92%, RR = 13.66, 95% CI = 3.5–53.35) from baseline. Likewise, the use of vedolizumab was followed by a significantly improved complete response (CR) at 12 months (pooled CR = 27.27%, RR = 5.50, 95% CI = 1.01–29.95), yet the CR at 14 days and 28 days did not reach statistical significance. Fifty-seven out of 87 (pooled overall survival, OS = 34.5%) and 46 out of 65 (pooled OS = 29.2%) patients expired at 6 and 12 months after the use of vedolizumab, respectively. Prophylactic use of vedolizumab was not associated with any specific type of reported adverse events, while patients with GI-aGVHD on vedolizumab presented with significantly increased risks of adverse events including infections (RR = 7.55) and impaired metabolism or nutritional complications (RR = 9.00). All analyses were of a low heterogeneity (all I-squares = 0%).ConclusionVedolizumab was safe and effective for the prophylaxis and management of early grade GI-aGVHD. More clinical evidence is warranted to validate these findings.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=345584, identifier CRD42022345584.